1972
DOI: 10.1111/j.1365-2133.1972.tb16186.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial Lichen Amyloidosis.

Abstract: Summary.— Nineteen members in 4 successive generations of one Chinese family in Malaysia were found to have classical lichen amyloidosis without systemic amyloid involvement. The disease was transmitted as an autosomal dominant trait with variable penetrance. Sex ratio was equal and the onset was around the age of puberty. The extent and severity of the lesions tended to increase with age. No patient subsequently developed the systemic form of amyloidosis. The present findings further strengthen the genetic th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…[28] Although most cases of PLCA are sporadic, 10% of cases have been reported to be familial. [323] Female preponderance has been consistently reported in the literature,[3614] except for a study by Black et al . which reported more males to be affected.…”
Section: Discussionmentioning
confidence: 99%
“…[28] Although most cases of PLCA are sporadic, 10% of cases have been reported to be familial. [323] Female preponderance has been consistently reported in the literature,[3614] except for a study by Black et al . which reported more males to be affected.…”
Section: Discussionmentioning
confidence: 99%
“…found cutaneous amyloidosis in members of four successive generations, suggesting an autosomal dominant mode of transmission. [16] Desouza reported four siblings with localized cutaneous amyloidosis. [17] However, Looi LM reported that most cases of primary cutaneous amyloidosis did not have a familial basis.…”
Section: Discussionmentioning
confidence: 99%
“…[2021] The overall positive family history of 17% in this study was similar to other studies, an observation that showed genetic predisposition and racial factor might contribute to a minor role in the occurrence of PCA. [222324]…”
Section: Discussionmentioning
confidence: 99%